2007
DOI: 10.1007/s10741-007-9025-2
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways in ischemic preconditioning

Abstract: Ischemic preconditioning renders the heart resistant to infarction from ischemia/reperfusion. Over the past two decades a great deal has been learned about preconditioning's mechanism. Adenosine, bradykinin, and opioids act in parallel to trigger the preconditioned state and do so by activating PKC. While adenosine couples directly to PKC through the phospholipases, bradykinin and opioids do so through a complex pathway that includes in order: phosphatidylinositol 3-kinase (PI3-kinase), Akt, nitric oxide synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
222
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(229 citation statements)
references
References 76 publications
0
222
1
4
Order By: Relevance
“…Over the next 2 decades extensive research further elucidated the temporal phases of IPC, the initiating triggers, and the other mechanistic aspects of this endogenous protective mechanism in diverse organs and species including humans; studies which are well summarized in recent reviews of this topic. [10][11][12][13][14][15] In laboratory animals and humans, IPC of the liver may be induced either by a single short period of ischemia or multiple short cycles of ischemia (or intermittent hilar clamping). 16 In a rat liver transplant model, Yin et al 2 investigated single IPC periods ranging between 5 and 20 minutes and showed that 10 minutes induced the best protection.…”
mentioning
confidence: 99%
“…Over the next 2 decades extensive research further elucidated the temporal phases of IPC, the initiating triggers, and the other mechanistic aspects of this endogenous protective mechanism in diverse organs and species including humans; studies which are well summarized in recent reviews of this topic. [10][11][12][13][14][15] In laboratory animals and humans, IPC of the liver may be induced either by a single short period of ischemia or multiple short cycles of ischemia (or intermittent hilar clamping). 16 In a rat liver transplant model, Yin et al 2 investigated single IPC periods ranging between 5 and 20 minutes and showed that 10 minutes induced the best protection.…”
mentioning
confidence: 99%
“…Intensive research has been performed on the signalling pathways. Several triggers, mediators, and effectors have been identified (Yellon 2003, Zaugg 2003, Downey 2007. The entire mechanism, or probably several pathways, has not been fully elucidated.…”
Section: Myocardial Preconditioningmentioning
confidence: 99%
“…The entire mechanism, or probably several pathways, has not been fully elucidated. One important key seems to be the ATP-sensitive potassium channels, KATP channels (Gross 2003, Yellon 2003, Zaugg 2003, Downey 2007. Experiments with different activators and inhibitors of these channels have demonstrated their role in inducing myocardial preconditioning when activated (Gross 2003, Yellon 2003.…”
Section: Myocardial Preconditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…These include activation of G protein-coupled receptors, protein kinase C, mitogen-activated protein kinases, ATPsensitive K + channels, heat shock protein, adenosine, metal ions, oxygen and nitrogen reactive species, oxidized and biological active lipids, cytokines, catecholamines, and nitric oxide (NO) synthase (7,8).…”
mentioning
confidence: 99%